Safety of lumbar puncture in comatose children with clinical features of cerebral malaria. (29th November 2016) - Moxon, Christopher A.; Zhao, Lei; Li, Chenxi; Seydel, Karl B.; MacCormick, Ian J.; Diggle, Peter J.; Mallewa, Macpherson; Solomon, Tom; Beare, Nicholas A.; Glover, Simon J.; Harding, Simon P.; Lewallen, Susan; et al.
Abstract : Objective: We assessed the independent association of lumbar puncture (LP) and death in Malawian children admitted to the hospital with the clinical features of cerebral malaria (CM). Methods: This was a retrospective cohort study in Malawian children with clinical features of CM. Allocation to LP was nonrandom and was associated with severity of illness. Propensity score–based analyses were used to adjust for this bias and assess the independent association between LP and mortality. Results: Data were available for 1, 075 children: 866 (80.6%) underwent LP and 209 (19.4%) did not. Unadjusted mortality rates were lower in children who underwent LP (15.3% vs 26.7% in the no-LP group) but differences in covariates between the 2 groups suggested bias in LP allocation. After propensity score matching, all covariates were balanced. Propensity score–based analyses showed no change in mortality rate associated with LP: by inverse probability weighting, the average risk reduction was 2.0% at 12 hours (95% confidence interval −1.5% to 5.5%, p = 0.27) and 1.7% during hospital admission (95% confidence interval −4.5% to 7.9%, p = 0.60). Undergoing LP did not change the risk of mortality in subanalyses of children with severe brain swelling on MRI or in those with papilledema. Conclusion: In comatose children with suspected CM who were clinically stable, we found no evidence that LP increases mortality, even in children with objective signs of raised intracranial pressure.